Prevalence of Iron Overload and Chelation Therapy in patients of Thalassemia Major and Knowledge and Attitude of Population towards Iron Chelation Therapy in Sargodha, Pakistan - Sadaf Liaquat, Um A Aiman, Javairia Amil, Saadia Javed, Nighat Fatima (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Whether familial or sporadic, whatever the cause may be, among hereditary hematological disorders, thalassemia accounts for 4.5 out of 10,000 live births worldwide1. Among other complications that these patients have, magnitude of transfusion related iron overload ranges from 9.5%-18%2. Prevalence of post transfusion iron overload in Southeast Asia is much higher than Western world3. Aim: To measure the prevalence of iron overload and chelation therapy in patients of thalassemia major and knowledge and attitude of population towards iron chelation therapy in Sargodha, Pakistan. Methods: This was a cross-sectional study conducted at Rai Hospital, a private-sector hospital and Hilal-e-Ahmar Hospital in Sargodha. Total 390 patients of beta thalassemia major aged 1 month-20 years were included in the study. Data Records of 390 patients of beta thalassemia major, confirmed on hemoglobin electrophoresis admitted in the hospital from June 2021 to June 2022 were included. Data were collected on socio-demographics clinical and laboratory profile. Analysis was done in SPSS Results: The mean age of the participants was 8.79 years, and 51.2 % were males and 48.9 % were females. Iron overload was found in 85.64% % of patients. Highest figure was 18,666ng/ml. Mean serum ferritin level was 3815 ng/ml. 30.2% received regular chelation therapy; 35.3%was on irregular chelation therapy and in 34.3% it was not started yet. Significant factors associated with iron overload and lack of chelation therapy were highly constrained socioeconomic status, repeated and frequent transfusions, lack of knowledge of importance of chelation therapy and unawareness of complications of transfusion. Conclusion: Considering the prevalence and perils of disease itself and treatment related complications government should focus on establishing thalassemia centers nationwide to cater problems faced by these patients where trained doctors and paramedical staff can counsel them regarding disease prognosis and importance of iron chelation therapy in course of disease. Keywords: Prevalence, iron overload, thalassemia major, chelation therapy